Super human [large type] : the bulletproof plan to age backward and maybe even live forever - Asprey, Dave (HarperLuxe, an imprint of HarperCollins Publishers, 2019)
While we tend to assume that our lives will follow a bell curve - peaking in middle age and gradually declining each year thereafter - Dave Asprey's research reveals there is another way. In "Super Human," he reveals how to make changes on the subcellular level to not only dramatically extend our lives, but also enhance quality of life. Using simple interventions that include nutrition, sleep, light therapy, exercise, and supplementation, as well as little-known but powerful technologies like ozone therapy and proper jaw alignment, you can decelerate cellular aging and super-charge your body's ability to heal and rejuvenate starting today. Asprey's "Super Human" arms readers with practical advice they can implement immediately to maximize the quality and quantity of their years. - back cover